Modern Trends in the Development of Robotic Complexes for Humanitarian Demining - Yanushkevych, D.; Ivanov, L. (ХНУРЕ, 2022)
The object of research is robotic military complexes used in the system of humanitarian demining. This work aims to study the requirements for robotic military complexes (including manipulators that are sucked into them) and to develop proposals for their use in humanitarian demining. The research is based on the application of a functional approach to the construction of models for the formation of requirements for robotic military complexes (RMC), which are sucked into the system of humanitarian demining.
Keywords: explosive object; robotic military complexes; humanitarian demining; mobile platform